Oleic acid attenuates asthma pathogenesis via Th1/Th2 immune cell modulation, TLR3/4-NF-κB-related inflammation suppression, and intrinsic apoptotic pathway induction - Lee, Soon-Young; Le, Duc Dat; Bae, Chun-Sik; Park, Jin Woo; Lee, Mina; Cho, Seung-Sik; Park, Dae-Hun (Frontiers in Immunology, 2024)
WHO reported that asthma was responsible for 455,000 deaths in 2019 and asthma patients was evaluated 262 million in May 2023. The incidence is expected to increase as the average life expectancy increases, highlighting asthma as a significant health challenge in an aging society. The etiology of asthma is linked to an imbalance of Th1 and Th2 cells, respiratory inflammation, and pulmonary cell proliferation. The purpose of this study is to investigate the anti-asthmatic effect and potential mechanism of oleic acid. The anti-inflammatory effect of oleic acid was evaluated in an LPS-induced RAW 264.7 cell model, and immune modulation and the anti-apoptotic effect were measured in an ovalbumin-induced BALB/c mouse model.A variety of analytical procedures, such as MTT, qPCR, ELISA, Western blotting, immunofluorescence, gene transfection, immunohistochemistry, and several staining methods (Diff Quik, H&E, PAS), were used to evaluate the effectiveness and mechanisms of these methods. The results from in vitro experiments showed that oleic acid could reduce the levels of inflammatory cytokines (TNF-α, IL-6, and IL-1β), and molecular docking studies suggested that oleic acid could interact with TLR3 and TLR4 proteins to form ligand-protein complexes, showing good binding affinity. Additionally, oleic acid attenuated the expression of MAPK pathway components (JNK, p38 MAPK) and NF-κB pathway constituents (IκB, NF-κB, COX-2, PGE2). In vivo results indicated that oleic acid reduced the levels of inflammatory cells (WBCs and eosinophils) and IgE activity, reduced the expression of the Th2 cell transcription factor GATA-3, and decreased the levels of Th2/Th17-related cytokines . Oleic acid also alleviated OVA-induced pathological changes in the lung, such as epithelial cell proliferation, inflammatory cell infiltration, and mucus hypersecretion. OVA restored apoptosis in lung epithelial cells by modulating the expression of Bcl-2 and Bax. In summary, oleic acid has potential as a novel candidate for asthma treatment through its ability to regulate immune cells, exert anti-inflammatory effects, and promote apoptosis, thereby ameliorating asthma manifestations.